Children of Patients Undergoing Psychiatric Treatment: An Investigation of Statutory Support Services After Referrals to Child Protection Services - Ranning, Anne; Hjorthøj, Carsten; Jensen, Kamilla B.; Ebsen, Frank Cloyd; Svendsen, Idamarie Leth; Thorup, Anne Amalie Elgaard; Nordentoft, Merete (Frontiers in Psychiatry, 2020)
Aims Preventive interventions for children of parents with mental illness are widely recommended. Mental health services entrust concern for patients’ children by referrals to child protection services. We investigated service coverage for children following referrals. Methods Data from referrals regarding 376 children of adult psychiatry patients over 2008-2012 was linked to information from municipal records and Danish national registers. We conducted Cox regression and used Kaplan Meier curves to show time to intervention and cumulative incidence of any child and family support services with one-year follow-up from referral date. Results At follow-up, 32% of children were provided with a child and family support service on average 73,4 days after referral. The most common services were family treatment (18%) and family counseling (11%). A statutory child assessment was conducted for 21% of children. Contents of the referrals suggested that 60% of children experienced adverse home environments and/or acute situations due to parents’ psychiatric illness. Predictors of initiation of support services included a child living alone with the patient, hazard ratio 2.09 (1.41-3.08), the patient being the mother, hazard ratio 1.72 (1.11-2.65), and an adverse home environment presenting an acute situation specified in referral, hazard ratio 1.89 (1.01-3.51). Conclusion Our finding that only one third of children receive support after referrals from psychiatry within an average of three months suggests an underserved population of at-risk children. These findings warrant reconsideration of resource allocation and creation of more efficient intervention strategies to protect at-risk children and prevent development of mental illness and adversity.